Spin and Pseudospin Symmetries with Trigonometric Pöschl-Teller Potential including Tensor Coupling - M. Hamzavi; A. A. Rajabi (Advances in High Energy Physics)
We study approximate analytical solutions of the Dirac equation with the trigonometric Pöschl-Teller (tPT) potential and a Coulomb-like tensor potential for arbitrary spin-orbit quantum number κ under the presence of exact spin and pseudospin (